1997
DOI: 10.1111/j.1937-5956.1997.tb00422.x
|View full text |Cite
|
Sign up to set email alerts
|

DEVELOPMENT AND R&D CAPABILITY AT MANUFACTURING SITES: ELECTRONICS MULTINATIONALS IN SINGAPORE AND TAIWAN

Abstract: In this paper we present the results of an empirical study of the manufacturing sites of foreign electronics companies in Singapore and Taiwan. The manufacturing and R&D capabilities at the sites are assessed. The way in which host government policies interact with R&D development at the sites and the speed of the R&D development are also considered. The results suggest that Singapore and Taiwan are now host to some advanced manufacturing and R&D operations. We show, however, that the product design work at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2000
2000
2006
2006

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…POM also published a paper that is concerned with the impact of government policy on technology strategy. In the summer of 1997, Tilley et al (1997) assessed and compared development capabilities of companies in Singapore and Taiwan, and they also studied the impact of government policy on the R&D capabilities of electronics companies in these countries. They found that national strategies in Singapore and Taiwan, especially tax holidays and R&D grants, contributed to the pace of development.…”
Section: Technology Strategy and Technology Managementmentioning
confidence: 99%
“…POM also published a paper that is concerned with the impact of government policy on technology strategy. In the summer of 1997, Tilley et al (1997) assessed and compared development capabilities of companies in Singapore and Taiwan, and they also studied the impact of government policy on the R&D capabilities of electronics companies in these countries. They found that national strategies in Singapore and Taiwan, especially tax holidays and R&D grants, contributed to the pace of development.…”
Section: Technology Strategy and Technology Managementmentioning
confidence: 99%